Past agricultural practices explain old field biodiversity and community composition in annually mowed grasslands: a case study of grazing and cultivation legacies in the northeastern United States - Alana M. Danieu; Theresa W. Ong (PeerJ)
The northeastern United States experienced extensive deforestation for agriculture expansion and nearly equal passive reforestation following agriculture abandonment across the region over the past century. Old fields provide critical habitat as grasslands in the Northeast but tend to return to forests without intervention unless land managers implement disturbance regimes to maintain grassland states in the region. The relative importance of past and present disturbances in old field plant communities remains poorly resolved, partly because management varies widely in these systems. This motivated the present case study, which compares two proximate old fields that benefit from long and consistent management practices both before and after agriculture was abandoned in Hanover, NH. One field experienced agricultural disturbances associated with grazing while the other experienced cultivation each for 116 years followed by 50 years of the same annual mowing disturbances after agriculture was abandoned. Diversity was higher, communities more convergent across sub-plots, and woody individuals three times more numerous in the grazed site, while soil texture, type, elevation, and drainage had no discernible impact. The study helps to clarify the different legacies of grazing and cultivation on old field plant community diversity and composition. Despite undergoing 50 years of mowing following agriculture abandonment, the two old fields have divergent communities that are more consistent with the intensity of historic agricultural practices at each site than with any differences in measured soil characteristics. Understanding how agricultural legacies combine with contemporary disturbance regimes to shape successional communities may improve conservation and restoration efforts of grassland habitats and other ecosystems undergoing rapid environmental change, with implications for biodiversity, ecosystem services, and resilience.